Phytochemical and ethnomedicinal study of Huperzia species used in the traditional medicine of Saraguros in Southern Ecuador; AChE and MAO inhibitory activity. (4th December 2016) - Armijos, Chabaco; Gilardoni, Gianluca; Amay, Luis; Lozano, Antonio; Bracco, Francesco; Ramirez, Jorge; Bec, Nicole; Larroque, Christian; Finzi, Paola Vita; Vidari, Giovanni
Abstract: Ethnobotanical and ethnomedicinal relevance: This study concerns seven Huperzia species (Lycopodiaceae), namely H. brevifolia, H. columnaris, H. compacta, H. crassa, H. espinosana, H. tetragona, H. weberbaueri, which are considered sacred plants by the Saraguro community, living in the Southern Andes of Ecuador; these plants are widely used in traditional medicine and ritual ceremonies. Material and methods: The plants were selected on the basis of written interviews with 10 visionary healers ( yachak ) (2 women, 8 men), indicated as the most credible by the Saraguro Healers Council. The Informant Consensus Factor ( F ic ) was determined. The first phytochemical study of the plants was performed by standard procedures, while the AChE and MAO-A inhibition by fractions enriched in high MW alkaloids, was measured in vitro. Aims of the study: i) to investigate the uses of some Huperzia plants in healing and magical-religious practices of Saraguros; ii) to identify the main components of plant hydromethanolic extracts; iiì) to test the effects of alkaloidal fractions on the activity of two enzymes linked to mental health. Results: All the interviewed Saraguro yachak showed a high consensus about the uses of the seven Huperzia plants as purgatives and against supernatural diseases, such as the " espanto " (startle). In admixtures with other plants, some species also induce a state of trance or hallucinations in participants in magical-religious rituals. GC–MS of the volatile alkaloid fractions allowed the identification of some lycodine-type and lycopodine-type alkaloids (1 -5 ) in H. compacta, H. columnaris, and H. tetragona . The flavones selgin) (6 ) and tricin (7 ) were isolated from H. brevifolia and H. espinosana . Tricin (7 ) was also detected in the other five species. The rare serratene triterpenes serratenediol (8 ) serratenediol-3- O -acetate (9 ), 21-episerratenediol (10 ), and 21-episerratenediol-3- O -acetate (11 ) were isolated from H. crassa . In addition, the presence of an unprecedented group of high molecular weight alkaloids has been determined. Alkaloid fractions of H. brevifolia, H. compacta, H. espinosana, and H. tetragona significantly inhibited AChE and MAO-A activities in vitro. Conclusions: The first phytochemical and ethnopharmacological study of seven Huperzia plants, widely used by Saraguro healers, led to the identification of several alkaloids and triterpenoids with different remarkable biological activities. In addition, alkaloid fractions exhibited a significant AChE and MAO-A inhibitory activity. These results may support the use of these plants in brews prepared for inducing psychoactive effects in participants in magical-religious ceremonies. This study confirms the rich traditional medical knowledge of Saraguro healers which must be documented and preserved for future generations. Graphical abstract: